Diverse Flavonoids from the Roots of Indigofera stachyodes. Issue 10 (26th September 2022) - Lou, Huayong; Liu, Hanfei; Wang, Huan; Zhao, Yumin; Huang, Lei; Fu, Jian; Hao, Xiaojiang; Pan, Weidong
Abstract: Three new flavonoids, 4′‐ O ‐ β ‐D‐glucopyranosyl‐2 S, 3 R ‐3, 7‐dihydroxy‐3′‐methoxyflavan (1 ), (3 R )‐7, 4′‐dihydroxy‐5, 3′‐methoxychalcone (2 ), (3 S )‐7, 2′, 3′‐trihydroxy‐6, 4′‐dimethoxylisoflavan (3 ), and one new natural occurring product, (3 S )‐6, 2′, 3′‐trihydroxy‐7, 4′‐dimethoxylisoflavan (4 ), together with eleven known ones (5 –15 ), were isolated from the roots of Indigofera stachyodes . The structures of these compounds were confirmed by UV, IR, MS, and NMR spectroscopic analysis. The absolute configurations of new compounds were elucidated by ECD spectra and chemical method. All the isolated flavonoids were screened for their antioxidant abilities to scavenge DPPH and ABTS + . As results, compounds 2 –4, 10, and 15 exhibited remarkable scavenging activity against both ABTS + and DPPH, with the IC50 values less than 20 μM. In addition, compounds 1, 6 –9, and 13 exhibited potential antioxidant scavenging activities, IC50 values were in the range of 17.96∼85.91 μM. Abstract :